Framing Sustainability as a Property of Software Quality. - LAGO, PATRICIA; AKINLI KOÇAK,, SEDEF; CRNKOVIC, IVICA; PENZENSTADLER, BIRGIT (Communications of the ACM, 2015)
The article focuses on case studies on sustainability in computer programming. The cases investigated were a paper mill's energy control system and a car-sharing service in Germany. The authors argue that creating a sustainability analysis framework will allow software developers to analyze the environmental and social aspects of their work and to balance this with technical and economic considerations. However, they note that sustainability requirements will add to the system scope and will necessitate more work during the requirements phase. INSET: Software Sustainability..